AB0328 Cardiovascular risk evaluation in long standing rheumatoid arthritis: real clinical data. (12th June 2018) - Babaeva, A.; Kalinina, E.V.; Zvonorenko, M.S.; Solodenkova, K.S.; Osadchuk, M.A.
Abstract : Background: According to recent national and EULAR recommendation cardiovascular risk (CVR) in pts with RA should be evaluated using modified SCORE system. But a lot of investigations and real clinical data demonstrate that this system commonly down-estimates CVR in RA pts. Objectives: Aim of our study was to compare standard CVR assessment and additional CVR evaluation on the basis of specific disease-associated risk factors (RF) and CV system investigations in long standing RA. Methods: 118 pts (96 female, 22 male) aged from 34 to 74 years old (mean age 55.91±5.21) with long standing RA (duration >5 years) were observed. In all pts CVR was stratified according to modified SCORE. We have analysed pts medical cards and standard examination data to determine clinical features of RA and associated conditions to verify severity of CVR. In term to reveal asymptomatic CV disease pts had undergone additional investigations (echocardiography, Dopplerography of carotid arteries, ECG-monitoring). Results: Conventional CVRF were registered in 110 (93.22%) pts. Age>45 (male), >50 (female) was in 85 (72.03%) pts, BMI>25 kg/m 2 ; in 10.17%, elevated cholesterol level and/or dyslipidemia in 41.52%, AH with target organ damage was detected in 45.76%, T2DM in 11.8%, CKD 3 stage in 10.17%, history of MI was in 2 (1.69%) pts. According to modified SCORE for RA very high, high, moderate and low CVR was detected in 17.80%, 47.46%, 18.64%, 16.10% cases respectively. High activity of RA was diagnosed in 61.02%, and erosive arthritis in 84.75% pts. Inadequate disease-modifying treatment was qualified in15.26% cases. Majority of pts (59.32%) received systemic glucocorticoids (GC) in daily doses from 2 to 12 mg of methylprednizolon, among these pts 14 (11.86%) have been taken GC in moderate and high dose for a long period. On the basis of instrumental data asymptomatic atherosclerosis of aorta and/or aortic valve and/or carotid arteries was detected in 44 pts (37.29%). Silent ischemia was revealed in 3 pts (2.54%). High disease activity and long term systemic GC treatment were associated with significantly high CV events in observed pts (p<0.05). Using obtained results we reassessed CVR in studied cohort. Revised data of CVR stratification suggest that 49 (41.53%) pts were in VH-CVR, 41 (34.75%) – in H-CVR, 16 (13.56%) in M-CVR and only 12 (10.17%) in L-CVR. The difference in pt ratio for CVR stratification was significant in accordance with χ 2 ; criterion. Conclusions: Obtained data suggest that modified SCORE is not absolutely reliable tool for precise CVR stratification in long standing RA. Additional investigations to define asymptomatic atherosclerosis and coronary artery disease are required in term to prevent CV complications especially in pts with high active erosive RA treated with systemic GC. Disclosure of Interest: None declared